Freedom as the elixir of life in Kate Chopin's fiction - Finatti, Rosemary Elza [UNESP] (Univ Estadual Paulista-unesp, 2022)
This paper seeks to analyze the theme of freedom as the elixir of life, weaving, in turn, a dialogue between the short stories Emancipation: A Fable of Life (1869-1870) and The Story of an Hour (1894), by the American author Kate Chopin. In both narratives, the symbolic setting that delineates the scenery of nature is opposed to the closed space of the cage and the house as a representation of social imprisonment. In this sense, the possibility of breaking through such barriers drives the characters' self-realization, both in the fabled universe represented by an animal that glimpses the possibility of being free and all the implications of the search for survival and in the protagonist Louise Mallard, who, faced with supposed widowhood, imagines a new life metaphorically awakened by the spring scenario. Contesting the imprisonment of individuality and perspectives of the characters confined in claustrophobic spaces, the short stories reveal the author's critical bias towards female limitations imposed by patriarchal ideology. To this end, the analyses will be guided by the considerations of Per Seyersted (1969, 1980), Betty Friedan (1971), Bernard Koloski (1996), among other authors.
Keywords: Emancipation; a fable of life; Kate Chopin; The story of an hour